Liquid Effluent Bioremediation Resorting to Microalgae Cultivation - Fernandes, Joana Batista Nunes (2023)
"Agricultural and industrial activities require extensive use of raw materials and generate large amounts of nutrient-rich waste streams. These have been linked to a drastic and widespread increase in the pollution of aquatic systems, and incidence of eutrophication events. The need to reduce nutrient runoffs and preserve the presently available water resources is a major concern and a great opportunity to develop nutrient removal and recovery processes for waste streams. Microalgae have been exploited for the treatment of different industrial wastewaters, coupling microalgal biomass production with resource recovery and waste valorisation, demonstrating the potential of microalgal-based systems to integrate a circular economy model.(...)"